2010
DOI: 10.1016/j.otohns.2010.06.817
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus in the elderly: Profile, correlates, and impact in the Nigerian Study of Ageing

Abstract: Tinnitus is common among elderly Nigerians and is associated with treatable health conditions, such as otitis media, rhinosinusitis, head injury, and hypertension. Its association with functional impairment and reduced quality of life highlights the need for inclusion in any comprehensive health care for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 22 publications
5
44
1
4
Order By: Relevance
“…3 The results of the study showed a prevalence of 10•1% among adults, with the tinnitus described as moderately annoying by 2•8% of respondents, severely annoying by 1•6%, and at a level that severely aff ected ability to lead a normal life by 0•5%. Results from studies in Egypt, 4 Japan, 5 and Nigeria, 6 indicate tinnitus prevalence is broadly similar in these countries to in Europe and the USA. The prevalence of troublesome tinnitus increases with age to 70 years; results of some studies show that it continues to increase thereafter, although others have shown it to diminish.…”
Section: Epidemiologymentioning
confidence: 87%
“…3 The results of the study showed a prevalence of 10•1% among adults, with the tinnitus described as moderately annoying by 2•8% of respondents, severely annoying by 1•6%, and at a level that severely aff ected ability to lead a normal life by 0•5%. Results from studies in Egypt, 4 Japan, 5 and Nigeria, 6 indicate tinnitus prevalence is broadly similar in these countries to in Europe and the USA. The prevalence of troublesome tinnitus increases with age to 70 years; results of some studies show that it continues to increase thereafter, although others have shown it to diminish.…”
Section: Epidemiologymentioning
confidence: 87%
“…Based on recent data, tinnitus occurs in 25.3% of American adults (50 million people) with 7.9% experiencing it frequently (16 million people) [5]. Epidemiological studies reveal comparable prevalence rates throughout Europe [6-9] and similarly high prevalence in Asia [10, 11] and Africa [12, 13] indicating that tinnitus is a significant health problem throughout the world.…”
Section: Tinnitus Is a World-wide Problem Of High Prevalence And Socimentioning
confidence: 99%
“…To our knowledge, only 20 previous studies from 14 countries reported information on adult tinnitus prevalence using surveys recorded at a national or sub-national level. Online supplementary table 1 (www.karger.com/doi/10.1159/000431376) shows the summary results from those surveys [5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Prevalence of tinnitus in adults ranged between 5 and 30% and that of severe tinnitus from less than 1 to 7%.…”
Section: Introductionmentioning
confidence: 99%